Carbon Dot Nanozymes: How to Be Close to Natural Enzymes. Issue 4 (12th December 2018) - Lv, Yang; Ma, Mingrou; Huang, Yucheng; Xia, Yunsheng
Abstract: The design, catalytic process, and property study of nanozymes are of importance for both fundamental research and application demand. Here, the peroxidase‐mimicking properties of a series of carbon dots (C‐dots) was systematically investigated and they were found to be probably closer to their natural counterparts, as compared to the known corresponding nanozymes. Firstly, four kinds of metal‐free and surface‐modulated C‐dots were bottom‐up fabricated using glucose, α‐cyclodextrin (CD), β‐CD, and γ‐CD as precursors, respectively, and their formation processes, structures, as well as surface chemistry were investigated. Secondly, in the peroxidase‐mimicking catalytic system, no hydroxyl radicals were produced, which indicates a different and special catalytic mode. By employing a joint experimental–theoretical study, a probable catalytic mechanism is proposed. Thirdly, the present C‐dots maintained well their catalytic activity even in complicated serum matrices because their catalytic performances are completely irrelevant of any cation‐related binding sites. Finally, the catalytic performances of the as‐prepared C‐dots were modulated by either pre‐engineering NP surface structures or subsequently introducing photo‐regulated host–guest reactions. Abstract : A specific nanozyme : As assessed by the combination of experimental and theoretical studies, the proposed carbon dots show a different and special peroxidase‐mimicking activity. Owing to the stronger anti‐interference capacity and versatilely modulated catalytic properties, they are closer to their natural counterparts as compared to the known corresponding nanozymes.